Oxide bulk material and applications and methods of improving thermoelectric material performance
Patent Information
- Application Number
- CN202210228764.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-03-09
AI Technical Summary
但其测量结果在一定程度上会受到被测物体发射率的影响,在测试时,需考虑测温探头在机匣上的安装位置、冷却方式等问题,不适用于测温探头不便安装的场合进行精准测温
[0024]1.提供一种氧化物块体材料及其制备方法,所述氧化物块体材料可作为薄膜热电偶中的高温热电材料使用,将这种氧化物块体材料应用在航空发动机的涡轮叶片上的测温薄膜热电偶之中,实现对工作涡轮叶片的精准测温。
Smart Images

Figure CN114649465B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermoelectric materials technology, and in particular to an oxide bulk material and its application, as well as a method for improving the performance of thermoelectric materials. Background Technology
[0002] As the heart of modern aircraft, aero-engines are currently undergoing continuous technological advancements towards higher performance and higher thrust-to-weight ratios. Turbine blades, as key components in aero-engines that convert thermal energy into mechanical energy, rotate at high speeds under the impact of high-temperature exhaust gases. Besides enduring immense stresses, they are also subject to high-temperature oxidation and thermal corrosion. Prolonged operation of turbine blades under these high-temperature, high-pressure, high-speed, and high-load conditions reduces the reliable service life of hot-end components, lowers material strength, leading to creep and even fracture in the hot-end materials, resulting in serious consequences. As the rotating component with the highest operating temperature in the engine, the temperature resistance of engine turbine blades directly determines flight speed and the generation of fighter jets. Therefore, accurately measuring the temperature changes of the blades during operation and researching and optimizing the high-temperature resistance of materials are crucial. Researchers have attempted to develop numerous temperature measurement technologies based on various principles to address the complex environment inside aero-engines. However, due to the high internal temperature, confined space, and high-speed rotation of the turbine blades, accurately measuring the temperature of turbine blades remains a challenge.
[0003] Currently, temperature measurement technologies for aero-engine turbine blades are mainly divided into two categories: contact temperature measurement and non-contact temperature measurement. Representative contact temperature measurement methods include thermocouple temperature measurement, crystal temperature measurement, and temperature-indicating paint temperature measurement; while representative non-contact temperature measurement methods include fluorescence temperature measurement, infrared radiation temperature measurement, and fiber optic temperature measurement. Although traditional contact temperature measurement technology is mature, it not only has a temperature measurement limit but also damages the blade structure and affects the target temperature field distribution. Furthermore, because it generally can only measure the temperature of the object being measured and the temperature sensor after reaching thermal equilibrium, the response time is relatively long, making it unsuitable for measuring the temperature of rapidly changing or small targets. On the other hand, infrared radiation temperature measurement, as a representative of non-contact temperature measurement, can measure not only rapidly changing temperature fields but also the surface temperature of high-speed rotating objects without contact with the object being measured, and its development is relatively mature. However, its measurement results are affected to some extent by the emissivity of the object being measured. During testing, the installation position of the temperature probe on the casing and the cooling method must be considered, making it unsuitable for accurate temperature measurement in situations where it is inconvenient to install the temperature probe. Summary of the Invention
[0004] To address the above problems, the present invention aims to provide a bulk oxide material and its preparation method, and to apply this bulk oxide material to a temperature-measuring thin-film thermocouple on the turbine blades of an aero-engine, thereby achieving precise temperature measurement of the working turbine blades. The method involves adjusting the ratio of La₂O₃, CuO, and BaO to control the temperature of the La₂O₃ material. 2-x Ba x The electrical conductivity, thermal conductivity, Seebeck coefficient, and carrier concentration of CuO4 oxide bulk materials are studied to improve the thermoelectric performance of oxide thermoelectric materials.
[0005] The first technical problem solved by this application is: to provide an oxide bulk material, wherein the oxide bulk material is La. 2-x Ba x CuO4 oxide bulk material.
[0006] Furthermore, the La 2-x Ba x In CuO4 oxide, 0 ≤ x ≤ 0.06.
[0007] In a preferred embodiment, La 2-x Ba x x = 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06 in CuO4 oxide.
[0008] The second technical problem solved by this application is: to provide an application of an oxide bulk material, wherein the oxide bulk material is used as a high-temperature thermoelectric material in a thin-film thermocouple.
[0009] The third technical problem addressed by this application is: providing a method for preparing an oxide bulk material, wherein the La 2-x Ba x CuO4 oxide bulk materials are prepared by combining mechanical alloying and discharge plasma sintering with heterovalent doping to produce bulk materials with different contents of Ba, Sr, and Pb.
[0010] Furthermore, the method for preparing the aforementioned oxide bulk material specifically includes the following steps:
[0011] S1. High-purity La2O3, CuO and BaO oxides are used as initial raw materials, and are mixed into powder in a certain proportion;
[0012] S2. Place the mixed powder into a ball mill jar and perform dry milling and wet milling in sequence;
[0013] S3. The mixed liquid obtained after wet milling is dried to obtain uniform nano powder in which La2O3, CuO and BaO are fully mixed;
[0014] S4. Place the powder into a mold, press it into a tablet shape using an electric powder tablet press, and place it into a crucible containing 99% alumina;
[0015] S5. Place the crucible into a box-type resistance furnace for heating and holding at that temperature, and then let it cool to room temperature with the furnace.
[0016] S6. Remove the sheet-like sample from the crucible, grind and sieve it to obtain La. 2-x Ba x CuO4 nanoparticles;
[0017] S7. La 2-x Ba x CuO4 nanoparticles were placed in a graphite mold, and the graphite mold was then sintered in a discharge plasma sintering furnace to finally obtain La. 2-x Ba x CuO4 oxide bulk material.
[0018] Furthermore, in the method for preparing the oxide bulk material, the certain proportion in step S1 is: La2O3: 0.97-1; CuO: 1; BaO: 0-0.06.
[0019] Furthermore, in the method for preparing an oxide bulk material, step S2 involves dry grinding at a speed of 100–500 rpm for 15 min–96 h; during wet grinding, argon gas is introduced into the inlet of the ball mill jar while anhydrous ethanol is injected into the outlet using a syringe as a medium for wet grinding, with a speed of 50–300 rpm and a time of 15 min–12 h.
[0020] Furthermore, in the method for preparing an oxide bulk material, the heating and holding process in the resistance furnace in step S5 involves first raising the temperature to 750-900°C at a rate of 50-150°C / h, then raising it to 800-950°C at a rate of 20-50°C / h, and holding it for 5-24 hours.
[0021] Furthermore, in the method for preparing an oxide bulk material, the abrasive in step S7 is a graphite mold with a diameter of 10-20 mm, the sintering environment is a vacuum with a vacuum degree of 4-7 Pa, the sintering temperature is 700-900℃, the holding time is 2-10 min, the sintering pressure is 20-60 MPa, and the heating rate is 50-200℃ / min.
[0022] The fourth technical problem addressed by this application is: to provide a method for improving the performance of thermoelectric materials, wherein in the preparation process of the aforementioned oxide bulk material, the ratio of La2O3, CuO, and BaO is adjusted to control the La content. 2-x Ba xThe electrical conductivity, thermal conductivity, Seebeck coefficient, and carrier concentration of CuO4 oxide bulk materials are analyzed to improve their thermoelectric performance.
[0023] The beneficial effects of this invention are as follows:
[0024] 1. An oxide bulk material and its preparation method are provided. The oxide bulk material can be used as a high-temperature thermoelectric material in a thin-film thermocouple. This oxide bulk material is applied to a temperature-measuring thin-film thermocouple on the turbine blade of an aero-engine to achieve accurate temperature measurement of the working turbine blade.
[0025] 2. By doping with different valence elements, the p-type semiconductor La can be significantly modulated. 2-x Ba x The carrier concentration and effective mass of CuO4 are increased, thereby improving its conductivity and power factor, ultimately enhancing its thermoelectric performance across the entire temperature range. Attached Figure Description
[0026] Figure 1 For La 2-x Ba x X-ray diffraction pattern of CuO4 bulk material
[0027] Figure 2 For La 2-x Ba x Electrical conductivity test chart of CuO4 bulk material
[0028] Figure 3 For La 2-x Ba x Seebeck coefficient test chart of CuO4 bulk material
[0029] Figure 4 For La 2-x Ba x Power factor test chart of CuO4 bulk material
[0030] Figure 5 For La 2-x Ba x Thermal conductivity test chart of CuO4 bulk material
[0031] Figure 6 For La 2-x Ba x ZT value test chart of CuO4 bulk material
[0032] Figure 7 For La 2-x Ba x Average ZT value test chart of CuO4 bulk material Detailed Implementation
[0033] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and specific examples.
[0034] Example 1
[0035] La 2-x Ba x In the preparation of CuO4 oxide bulk material, x = 0 in this embodiment.
[0036] Step 1: Using high-purity La2O3, CuO and BaO oxides as initial raw materials, mix them in a ratio of La2O3:CuO:BaO = 1:1:0. Place the mixed powder into a ball mill jar and ball mill it in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0037] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0038] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0039] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0040] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0041] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x=0) nanoparticles.
[0042] Step 7: Combine the La synthesized in step 6 2-x Ba xCuO4 (x=0) nanoparticles were loaded into a 15mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions (5Pa). Sintering was carried out at specific temperatures, pressures, and holding times: 800℃ for 10min, 50MPa for 10min, and a heating rate of 100℃ / min. The final product was a La nanoparticle with a diameter of 15mm and a height of 10mm. 2-x Ba x CuO4 (x=0) oxide bulk material.
[0043] Example 2
[0044] La 2-x Ba x In this embodiment, x = 0.01, CuO4 oxide bulk material is prepared.
[0045] Step 1: Use high-purity La2O3, CuO and BaO oxides as initial raw materials. Mix them according to the ratio of La2O3:CuO:BaO = 0.995:1:0.01. Place the mixed powder into a ball mill jar and ball mill it in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0046] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0047] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0048] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0049] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0050] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x = 0.01) nanoparticles.
[0051] Step 7: Combine the La synthesized in step 6 2-x Ba x CuO4 (x = 0.01) nanoparticles were loaded into a 15mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions of 5 Pa. Sintering was carried out at specific temperatures, pressures, and holding times: 800℃ for 10 minutes, 50MPa for 10 minutes, and a heating rate of 100℃ / min. The final product was a La nanoparticle with a diameter of 15mm and a height of 10mm. 2-x Ba x CuO4 (x = 0.01) oxide bulk material.
[0052] Example 3
[0053] La 2-x Ba x In this embodiment, x = 0.02, CuO4 oxide bulk material is prepared.
[0054] Step 1: Using high-purity La2O3, CuO and BaO oxides as initial raw materials, and mixing them in a ratio of La2O3:CuO:BaO = 0.99:1:0.02, the mixed powder is placed in a ball mill jar and ball milled in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0055] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0056] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0057] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0058] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0059] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x = 0.02) nanoparticles.
[0060] Step 7: Combine the La synthesized in step 6 2-x Ba x CuO4 (x = 0.02) nanoparticles were loaded into a 15 mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions of 5 Pa. Sintering was carried out at specific temperatures, pressures, and holding times: 800 °C for 10 min, 50 MPa for 10 min, and a heating rate of 100 °C / min. The final product was a La nanoparticle with a diameter of 15 mm and a height of 10 mm. 2-x Ba x CuO4 (x = 0.02) oxide bulk material.
[0061] Example 4
[0062] La 2-x Ba x In this embodiment, x = 0.03, the CuO4 oxide bulk material is prepared.
[0063] Step 1: Use high-purity La2O3, CuO and BaO oxides as initial raw materials, and mix them in a ratio of La2O3:CuO:BaO = 0.985:1:0.03. Place the mixed powder into a ball mill jar and ball mill it in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0064] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0065] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0066] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0067] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0068] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x = 0.03) nanoparticles.
[0069] Step 7: Combine the La synthesized in step 6 2-x Ba x CuO4 (x = 0.03) nanoparticles were loaded into a 15 mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions (5 Pa). Sintering was carried out at specific temperatures, pressures, and holding times: 8000℃ for 10 min, 50 MPa for 10 min, and a heating rate of 100℃ / min. The final product was a La nanoparticle with a diameter of 15 mm and a height of 10 mm. 2-x Ba x CuO4 (x = 0.03) oxide bulk material.
[0070] Example 5
[0071] La 2-x Ba x In this embodiment, x = 0.04, CuO4 oxide bulk material is prepared.
[0072] Step 1: Using high-purity La2O3, CuO and BaO oxides as initial raw materials, and mixing them in a ratio of La2O3:CuO:BaO = 0.98:1:0.04, the mixed powder is placed in a ball mill jar and ball milled in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0073] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0074] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0075] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0076] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0077] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x = 0.04) nanoparticles.
[0078] Step 7: Combine the La synthesized in step 6 2-x Ba x CuO4 (x = 0.04) nanoparticles were loaded into a 15mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions (5 Pa). Sintering was carried out at specific temperatures, pressures, and holding times: 800℃ for 10 minutes, 50MPa for 10 minutes, and a heating rate of 100℃ / min. The final product was a La nanoparticle with a diameter of 15mm and a height of 10mm. 2-x Ba x CuO4 (x = 0.04) oxide bulk material.
[0079] Example 6
[0080] La 2-x Ba x In this embodiment, x = 0.05, CuO4 oxide bulk material is prepared.
[0081] Step 1: Use high-purity La2O3, CuO and BaO oxides as initial raw materials, and mix them in a ratio of La2O3:CuO:BaO = 0.975:1:0.05. Place the mixed powder into a ball mill jar and ball mill it in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0082] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0083] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0084] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0085] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0086] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x = 0.05) nanoparticles.
[0087] Step 7: Combine the La synthesized in step 6 2-x Ba x CuO4 (x = 0.05) nanoparticles were loaded into a 15 mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions of 5 Pa. Sintering was carried out at specific temperatures, pressures, and holding times: 800 °C for 10 min, 50 MPa for 10 min, and a heating rate of 100 °C / min. The final product was a La nanoparticle with a diameter of 15 mm and a height of 10 mm. 2-x Ba x CuO4 (x = 0.05) oxide bulk material.
[0088] Example 7
[0089] La 2-x Ba x In this embodiment, x = 0.06, CuO4 oxide bulk material is prepared.
[0090] Step 1: Using high-purity La2O3, CuO and BaO oxides as initial raw materials, and mixing them in a ratio of La2O3:CuO:BaO = 0.97:1:0.03, the mixed powder is placed in a ball mill jar and ball milled in an inert gas (argon) atmosphere at a speed of 300 rpm for 300 min.
[0091] Step 2: After dry grinding, while introducing argon gas into the inlet, inject anhydrous ethanol into the outlet using a syringe as a medium for wet grinding. The wet grinding speed is 300 rpm and the time is 300 min to obtain a mixed liquid.
[0092] Step 3: Dry the obtained mixed liquid at 50℃ for 10 hours to obtain a uniform nanoparticle powder that is fully mixed with La2O3, CuO and BaO.
[0093] Step 4: Place the obtained powder into a mold with a diameter of 12.5 mm, and press it into a cylindrical tablet with a diameter of 12.5 mm and a height of 10 mm under the pressure of 50 MPa using an electric powder tablet press. Place the tablet evenly into a corundum crucible containing 99% alumina and cover the crucible.
[0094] Step 5: Place the crucible containing the sheet sample evenly into the box-type resistance furnace. The temperature control program of the resistance furnace is as follows: first, heat up to 850℃ at a rate of 100℃ / h, then heat up to 900℃ at a rate of 50℃ / h, hold for 12 hours, and then cool down to room temperature with the furnace.
[0095] Step 6: Remove the sheet-like sample obtained after the solid-state reaction in Step 5 from the alumina crucible, grind it into powder using a mortar and pestle, and then sieve it through a 200-mesh sieve to finally obtain La. 2-x Ba x CuO4 (x = 0.06) nanoparticles.
[0096] Step 7: Combine the La synthesized in step 6 2-x Ba x CuO4 (x = 0.06) nanoparticles were loaded into a 15 mm diameter graphite mold and sintered in a discharge plasma sintering furnace under vacuum conditions (5 Pa). Sintering was carried out at specific temperature, pressure, and holding time: 800 °C for 10 min, 50 MPa for 10 min, and a heating rate of 100 °C / min. The final product was a La nanoparticle with a diameter of 15 mm and a height of 10 mm. 2-x Ba x CuO4 (x = 0.06) oxide bulk material.
[0097] La obtained from Examples 1-7 2-x Ba x X-ray analysis was performed on the bulk CuO4 oxide material, and the specific analysis is as follows:
[0098] Figure 1This indicates that the process involves dry grinding for 300 minutes at 300 rpm, followed by wet grinding for 300 minutes. After drying, the temperature is increased to 850℃ at a rate of 100℃ / h, then to 900℃ at a rate of 50℃ / h. The temperature is held for 12 hours, then cooled to room temperature in the furnace. The resulting La is obtained after grinding and sieving. 2-x Ba x La was obtained by heating CuO4 powder to 800℃ at a rate of 100℃ / min under a pressure of 50MPa and holding for 10min. 2-x Ba x X-ray diffraction pattern of CuO4 (x = 0 / 0.01 / 0.02 / 0.03 / 0.04 / 0.05 / 0.06) bulk material.
[0099] The performance of the La2-xBaxCuO4 oxide bulk materials obtained in Examples 1-7 was analyzed, and the specific analysis is as follows:
[0100] The La obtained in Examples 1-7 2-x Ba x The CuO4 bulk material was cut into regular cubes using a cutting machine and the surface was polished with sandpaper before being tested for thermoelectric properties, including electrical conductivity (σ) and Seebeck coefficient (α).
[0101] α 2 |
[0102] Based on the measured data above, the electrical properties of the material are evaluated using the power factor ( ). Figure 2 , Figure 3 and Figure 4 La 2-x Ba x The electrical conductivity, Seebeck coefficient, and power factor of bulk CuO4 materials. In addition, thermoelectric properties include the thermal diffusivity (D) and specific heat capacity (C). p Based on the measured data and the material's density (ρ), the total thermal conductivity (κ=D·C) can be used to determine the thermal conductivity. p ·ρ) is used to represent the thermal properties of a material. Figure 5 For La 2-x Ba x Total thermal conductivity of CuO4 thermoelectric materials Figure 6 For La 2-x Ba x ZT value of CuO4 thermoelectric material Figure 7 For La 2-x Ba x The average ZT value of CuO4 thermoelectric material.
[0103] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that those skilled in the art can make various modifications, combinations, and improvements to the above embodiments without departing from the concept of this patent, and these modifications and combinations all fall within the scope of protection of this patent. Therefore, the scope of protection of this patent should be determined by the claims.
Claims
1. An oxide bulk material for use as a high-temperature thermoelectric material in thin-film thermocouples, characterized in that, The oxide bulk material is La. 2-x Ba x CuO4 oxide bulk material, wherein 0.05≤x≤0.06; The material is prepared by the following method: 1) Mix high-purity La2O3, CuO and BaO into powder in the ratio of La2O3:CuO:BaO = (0.97-1):1:(0-0.06); 2) The mixed powder is subjected to dry grinding and wet grinding in sequence. The dry grinding speed is 100-500 rpm and the time is 15 min-96 h. During wet grinding, argon gas is introduced into the gas inlet of the ball mill jar, and anhydrous ethanol is injected into the gas outlet with a syringe as a medium for wet grinding. The wet grinding speed is 50-300 rpm and the time is 15 min-12 h. 3) The mixed liquid obtained after wet milling is dried to obtain uniform nano powder in which La2O3, CuO and BaO are fully mixed; 4) Place the powder into a mold, press it into a tablet shape using an electric powder tablet press, and place it into a crucible containing 99% alumina; 5) Place the crucible in a box-type resistance furnace for heating and holding, and then cool it to room temperature with the resistance furnace. The heating and holding in the resistance furnace is carried out by first raising the temperature to 750-900℃ at a rate of 50-150℃ / h, and then raising the temperature to 800-950℃ at a rate of 20-50℃ / h, and holding for 5-24 hours. 6) Remove the sheet-like sample from the crucible, grind and sieve it to obtain La. 2-x Ba x CuO4 nanopowder; 7) La 2-x Ba x CuO4 nanoparticles were placed in a graphite mold, and the graphite mold was then sintered in a discharge plasma sintering furnace to finally obtain La. 2-x Ba x CuO4 oxide bulk material, the mold is a graphite mold with a diameter of 10-20 mm, the sintering environment is vacuum with a vacuum degree of 4-7 Pa, the sintering temperature is 700-900℃, the holding time is 2-10 min, the sintering pressure is 20-60 MPa, and the heating rate is 50-200℃ / min.
2. A method for improving the performance of thermoelectric materials, characterized in that, Using the La as described in claim 1 2-x Ba x CuO4 oxide bulk material, by adjusting the ratio of La2O3, CuO and BaO, the La content was controlled. 2-x Ba x The electrical conductivity, thermal conductivity, Seebeck coefficient, and carrier concentration of CuO4 oxide bulk materials are analyzed to improve their thermoelectric performance.